Using a functional ontology of reputation to interoperate different agent reputation models - Casare,Sara (2005)
This paper presents a Functional Ontology of Reputation that could be used as a common shared reputation knowledge by agents. Although there is a huge work on agent reputation, each research defines its own basic concepts. Sometimes different meanings are associated to the same term and in other occasions the same meaning is related to different terms. We claim that the reputation knowledge structured as an ontology could be used to enable the semantic integration level involved in the interoperation of software agents using different reputation models. We have illustrated this idea by showing a semantic mapping for the reputation concepts used in three distinct reputation models. That mapping shows how this ontology could act as a common global ontology that supports the semantic integration among these models.